2024
DOI: 10.3389/fimmu.2023.1332213
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of neoadjuvant PD-1 inhibitors or PD-L1 inhibitors for muscle invasive bladder cancer: a systematic review and meta-analysis

Shibo Huang,
Yanping Huang,
Chunyan Li
et al.

Abstract: IntroductionThis meta-analysis aims to evaluate the efficacy and safety of neoadjuvant PD-1 inhibitors or PD-L1 inhibitors [PD-(L)1 inhibitors] for muscle-invasive bladder carcinoma (MIBC).Materials and methodsFour databases (Medline, Embase, Web of Science, and 21 CENTRAL) were searched for articles studying neoadjuvant PD-(L)1 inhibitors for MIBC. The search time period was from the establishment of each database to 21 July 2023. Meta-analyses of pCR, pPR, Grade≥ 3 irAEs rate, RFS, and OS were performed.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Currently, ICI (including PD-1 and PD-L1 inhibitors) are administered either as maintenance therapy for patients treated with first-line platinum-based chemotherapy who do not experience disease progression, or as first-line regimen for those patients ineligible to receive cisplatin [20,21]. According to a timely systematic review and meta-analysis on the efficacy of ICI in MIBC [22], PD-L1 inhibitors are less effective alone than in combination with other ICI or chemotherapeutic agents in terms of lower, complete, or partial, pathological response, yet they are associated with severe immune-related adverse effects. As BC patients treated with PD-L1 inhibitors show favorable OS and RFS, this treatment seems to be a promising therapeutic option for selected MIBC patients, highlighting the need to find feasible biomarkers.…”
Section: Pd-l1 In Bladder Cancer: Clinical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, ICI (including PD-1 and PD-L1 inhibitors) are administered either as maintenance therapy for patients treated with first-line platinum-based chemotherapy who do not experience disease progression, or as first-line regimen for those patients ineligible to receive cisplatin [20,21]. According to a timely systematic review and meta-analysis on the efficacy of ICI in MIBC [22], PD-L1 inhibitors are less effective alone than in combination with other ICI or chemotherapeutic agents in terms of lower, complete, or partial, pathological response, yet they are associated with severe immune-related adverse effects. As BC patients treated with PD-L1 inhibitors show favorable OS and RFS, this treatment seems to be a promising therapeutic option for selected MIBC patients, highlighting the need to find feasible biomarkers.…”
Section: Pd-l1 In Bladder Cancer: Clinical Implicationsmentioning
confidence: 99%
“…While some authors have revealed worse survival rates in BC patients with elevated PD-L1 expression [34][35][36][37][38], others have failed to find such a correlation [39,40]. The prognostic role of PD-L1 has recently been the subject of five meta-analyses over a few recent years (2019-2022), with a variable number of studies [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and cases (1393-4032) assessed in each analysis due to different eligibility criteria and search strategy variables (including databases, interval time, and MeSH terms) [41][42][43][44][45] (Supplementary Table S1). The authors found a statistically significant association overall between the expression of TC PD-L1 and poorer outcome parameters.…”
Section: Prognostic Role Of Pd-l1 In Bc: the Big Picturementioning
confidence: 99%